Pengaruh Keterikatan Karyawan Terhadap Kinerja Karyawan Dengan Keadilan Organisasi Sebagai Variabel Modertasi (Pada Hotel Pasterur Bandung) - Ramadhan, Faiz Akbar; Adriani, Zulfina; Chairunnisa, Fitri (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This study aims to and analyze if influence of employee engangement on employee performance trought organizational justice as a moderation. This study used the quantitative method, data collection techniques used by distributing questionnaires to 50 respondents. Hypothesis testing was carried out using the Structural Equtions Model (SEM) technique with the smartPLS 3.3.9 program. The results of the study show that : 1) employee engagement has a positive and significant effect of employee performance, 2) employee engagement has a positive and significant efffect on organizational justice, 3) organizational justice has a negative but not significant effect on employee performance, 4) organizational justice is not able to moderate the influence of employee engagement on employee performace.